A TRADITIONAL HERBAL MEDICINE : PRODUCT BRANDING TRAINING "JANDASARE" FOR MARKETING EXPANSION IN THE DIGITAL MARKET - Nurwijayanto, Putra Ramadhani; Dyah Setyawati; Theofilus Shalom (Community Development Journal, 2024)
This activity arises from an awareness of the great potential of traditional herbal medicine, which has long been an important part of Indonesian culture. In this case, the Sukun sub-district turns out to have hidden potential in the form of the traditional herbal medicine product "Jandasare". However, due to limited knowledge of digital marketing and branding, coupled with the fact that the market for traditional herbal medicine is becoming increasingly limited, especially among the younger generation, products from the Sukun sub-district are less considered for consumption. The community activity in the Sukun sub-district includes a series of steps, starting from market and competitor analysis, redesigning product packaging, to training producers in digital marketing. We also conducted digital marketing implementation by selling products online through Instagram Live to increase public understanding of the benefits of traditional herbal medicine. The results of this activity show a significant increase in public knowledge about the benefits of traditional herbal medicine and its use. A more modern and informative packaging design also increased consumer interest, especially among the younger generation. Additionally, herbal medicine producers have successfully improved product quality and used online platforms to market products more effectively. The importance of adapting traditional herbal medicine to the modern market is highlighted. Through rebranding and digital marketing changes, Jandasare herbal medicine is able to bridge the gap between tradition and contemporary development, proving that cultural heritage can remain relevant in the digital age. This community service activity has successfully mobilized economic potential in the Sukun sub-district through empowering traditional herbal medicine producers and increasing consumer interest. This demonstrates that branding strategies and marketing digitalization are key to maintaining and advancing traditional products in the modern era.